Accelerating Sustainable Development Goals for South African adolescents from high HIV prevalence areas: a longitudinal path analysis - Franziska Meinck; Mark Orkin; Lucie Cluver (BMC Medicine, 2021)
Abstract Background Adolescents experience a multitude of vulnerabilities which need to be addressed in order to achieve the Sustainable Development Goals (SDGs). In sub-Saharan Africa, adolescents experience high burden of HIV, violence exposure, poverty, and poor mental and physical health. This study aimed to identify interventions and circumstances associated with three or more targets (“accelerators”) within multiple SDGs relating to HIV-affected adolescents and examine cumulative effects on outcomes. Methods Prospective longitudinal data from 3401 adolescents from randomly selected census enumeration areas in two provinces with > 30% HIV prevalence carried out in 2010/11 and 2011/12 were used to examine six hypothesized accelerators (positive parenting, parental monitoring, free schooling, teacher support, food sufficiency and HIV-negative/asymptomatic caregiver) targeting twelve outcomes across four SDGs, using a multivariate (multiple outcome) path model with correlated outcomes controlling for outcome at baseline and socio-demographics. The study corrected for multiple-hypothesis testing and tested measurement invariance across sex. Percentage predicted probabilities of occurrence of the outcome in the presence of the significant accelerators were also calculated. Results Sample mean age was 13.7 years at baseline, 56.6% were female. Positive parenting, parental monitoring, food sufficiency and AIDS-free caregiver were variously associated with reductions on ten outcomes. The model was gender invariant. AIDS-free caregiver was associated with the largest reductions. Combinations of accelerators resulted in a percentage reduction of risk of up to 40%. Conclusion Positive parenting, parental monitoring, food sufficiency and AIDS-free caregivers by themselves and in combination improve adolescent outcomes across ten SDG targets. These could translate to the corresponding real-world interventions parenting programmes, cash transfers and universal access to antiretroviral treatment, which when provided together, may help governments in sub-Saharan Africa more economically to reach their SDG targets.